Diversidade, sazonalidade e uso de hábitat da comunidade de aves de rapina diurnas na região do Planalto das Araucárias, RS - Aver, Gustavo Francisco (Universidade do Vale do Rio dos Sinos, 2014)
The raptors, like other predators, have great importance in the regulation of prey populations and therefore influence the maintenance of ecosystems which are included. So, the presence of these individuals produces effects along the trophic chains influencing even the plant community involved. Because of that, knowing the communities of raptors, and also to evaluate how these taxa interact with changes to the environments in which they live, can explain the adaptability of these species. In particular, analysis of the choice of different places for these birds, elucidate which features of the environment are essential to the permanence of these individuals that the habitat. Thus, this study evaluated the community of diurnal birds of prey in a fragmented environment in the south of the Araucaria Plateau, analyzing characteristics of community structure and seasonality, as well as use and habitat selection tendency in relation to a heterogeneous environment with the presence of human action. In the study area were classified four distinct environments (native grassland, agricultural, native forest and planting of Pinus sp.) And were evaluated 3 fragments of each of these habitats. To survey the diurnal raptors three sampling points was performed on each of the 12 fragments. As a complementary methodology, there were 8 car transects along the study area, covering the four areas described habitats. We recorded 16 species of raptors, which showed significant differences in abundance throughout the seasons, which may be due to climatic differences that alter the resources available in the environment. The diurnal birds of prey used different environments to perform their behaviors and therefore no similarity was found in species composition in relation to the sampling points. Regarding the use of environments, the species used the open areas in greater quantities, with great use of agricultural environments, which confirms the adaptation of these individuals to these areas. The generalist species used, in general, environments in the proportion available in the area even featuring, in some cases, significant and positive selection to altered environments, emphasizing adaptation to environmental changes. On the other hand, some specialists species showed use of the most conserved areas and can therefore be used as indicator species of environmental quality.
Keywords: Floresta ombrófila mista; Accipitriformes; Falconiformes; Catharthiformes; Atlantic forest biome; Highlands of South Brazil; ACCNPQ::Ciências Biológicas::Biologia Geral